Socioeconomic Environment and Mortality: A two-level Decomposition by Sex and Cause of Death - Martin Gächter; Engelbert Theurl (University of Innsbruck, Department of Public Finance, 2010)
Gender inequalities in longevity/mortality are a major area of research since the 1970s. Despite substantial insights, the questions posed and the research strategies used are still in a state of flux. In the present paper we shed some light on the question, to which extent socioeconomic variables determine the gender gap in mortality for important causes of death. Thereby we specifically focus on behavior-related causes of death. We follow an ecological approach based on aggregated mortality data from Austria both at the community and the district level covering the time period 1969 - 2004. By using weighted regression analysis (panel fixed effects, pooled and cross section) we find that higher income levels reduce male mortality in most causes of death (including malignant neoplasms and diseases of the circulatory system), while this indicator appear to be insignificant for female mortality in these causes. This indicates that the decreasing effect of the higher socioeconomic status on mortality might be canceled out by a gender role equalization effect for women due to the adoption of unhealthy life styles (e.g. smoking). This finding is also confirmed by the fact that female mortality does not decrease with increasing income levels for smoking-related diseases, ischaemic heart disease and lung cancer. Thus, our results suggest that the decreasing female mortality advantage is mainly caused by increased smoking among women, while in the case of alcohol, violence and accidents the gender equalization seems to work in the opposite direction. In a nutshell, we conclude that the examination of the gender-specific mortality rates and mortality gaps without a disaggregation between different causes of death might mask important patterns of the epidemiological transition and the underlying drivers.
Keywords: I12; I18; J16; 330; mortality; gender differential; causes of death; life expectancy; Austria; Sterblichkeit; Geschlecht; Österreich